The Correlation between Poor Sleep Quality with Academic Stress Level in Medical Profession Students of Cenderawasih University, Jayapura - Setyarini, Kaida Irma; Sitanggang, Prysta Aderlia (PT FORMOSA CENDEKIA GLOBAL, 2024)
Mental health problems are psychological conditions that threaten various groups of society, including medical students. Sleep quality are thought to correlate with stress levels. This study aims to explore academic stress in medicine profession students, with 70 respondents. Sleep quality was measured using the Pittsburgh Sleep Quality. This study is a quantitative research with a cross sectional design, Pearson correlation test are used. The results showed that out of 70 respondents, there were 34 (48.6%) experienced moderate-severe stress levels, and 36 people (51.4%) experienced normal-light stress levels. The Pearson correlation test showed a value of p = 0.00 (significant) so that it was concluded that there was a correlation between poor sleep quality and the level of academic stress.